2015
DOI: 10.4014/jmb.1406.06045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Additives on the Thermal Stability of Glucoamylase from Aspergillus niger

Abstract: GAM-1 and GAM-2, two themostable glucoamylases from Aspergillus niger B-30, possess different molecular masses, glycosylation, and thermal stability. In the present study, the effects of additives on the thermal inactivation of GAM-1 and GAM-2 were investigated. The half-lives of GAM-1 and GAM-2 at 70°C were 45 and 216 min, respectively. Data obtained from fluorescence spectroscopy, circular dichroism spectroscopy, UV absorption spectroscopy, and dynamic light scattering demonstrated that during the thermal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Far-UV CD spectral measurement was performed as described previously [22]. The CD spectra in the range of 195–240 nm were determined on a JASCO J-715 spectropolarimeter (Jasco, Tokyo, Japan) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Far-UV CD spectral measurement was performed as described previously [22]. The CD spectra in the range of 195–240 nm were determined on a JASCO J-715 spectropolarimeter (Jasco, Tokyo, Japan) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, at a higher concentration of glycerol, the protein residual activity was reduced, compared to lower concentrations. High concentrations of viscosity-generating solutes can affect the enzyme s Michaelis-Menten constant [40][41][42], therefore affecting the catalytic efficiency [42,43]. However, the effect of glycerol was different when samples of rPON2 were stored in 20% glycerol at −20 °C.…”
Section: Protein Stabilizationmentioning
confidence: 99%
“…It indicates that the high temperature associated with extreme pH (in relation to the optimum conditions) promotes the loss of enzymatic activity (Vandersall, Cameron, Nairn, Yelenosky, & Wodzinski, 1995;Liu et al, 2015). Liu et al (2015) demonstrated that heating at temperatures ≥ 70°C promotes unfolding of the α-helix, which is often correlated with the loss of activity. In addition, at high temperatures, tryptophan residues were partially exposed, indicating changes in the tertiary structure of the enzyme.…”
Section: Determination Of Amyloglucosidase Activity and Optimum Ph Anmentioning
confidence: 99%